PENJARANGAN BUAH ANGGUR "BS-6" DENGAN PEMETIKAN BUAH DAN PEMOTONGAN TANDAN - Winarso D. Widodo; Sri Setyati Harjadi; G. A. Wattimena; A. A. Mattjik (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
An experiment consists of two separated trial sets had been carried out at Probolinggo, East Java to study of manual thinning on berry cluster of "BS-6" grape by berry removal and cluster tipping. Berry thinning severities that were investigated consists of berry-removing and cluster tipping, each applied control, 20%, 40% and 60% thinning treatments at 7 or 14 days after anthesis. Berry removal did not influence to berry density but increased large-berry proportion and juice quality; since cluster tipping increased berry density, berry size and berry uniformity. Manual thinning at 7 days after anthesis gave better effect than at 14 days after anthesis